A comparison of the online distance learning and traditional learning methods in enhancing nursing students knowledge and skills in using Glasgow Coma Scale (GCS) / Norimah Said … [et al.] - Said, Norimah; N., Nurul Hasdiyanti; AB, Junaidah; Ab Hamid, Mohd Ramlan (UiTM Press, 2018)
Online education is currently one of the best practices for online distance learning students (e-PJJ) when combined with traditional learning. The evolution of advanced nursing education and practice has been influenced by changes in methods of teaching including online learning, blended learning and traditional learning. The Glasgow Coma Scale (GCS)are knowledge and skill required by nursing students that are integral towards assessing the level of consciousness of patients with neurological injuries. This is because nurses play a vital role in minimizing the risk of deficiency and detecting early signs of Glasgow Coma Scale. The purpose of this study is to assess the knowledge and skills of nursing students in UniversitiTeknologi Mara (UiTM) PuncakAlam regarding Glasgow Coma Scale (GCS) and the differences between using online learning and traditional learning methods. A cross-sectional study using self-reported questionnaires was conducted among 125 undergraduate nursing students. The data were analyzed using SPSS version 21.0. On average, a full time undergraduate student has a higher level of knowledge compared to online distance-learning undergraduates (t=3.932, df=123,p<0.05). However, for the performance of the skill between fulltime nursing and online distance learning (e-PJJ), the latter students obtained a higher score for the correct item as compared to fulltime nursing students at (t=3.782, df = 131, p<0.05). Online learning is useful for distance learning students because they have experience in daily nursing practices and skills of GCS. However, there needs to be improvements to their knowledge to maintain their competency in nursing practice. That being said, full-time students need traditional and blended learning to enhance their knowledge and skills on GCS.